2021
DOI: 10.1210/clinem/dgab739
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Features in Adults With X-linked Hypophosphatemia: An Analysis of Clinical Trial and Survey Data

Abstract: Purpose To describe the burden of musculoskeletal features and associated surgeries across the lifespan of adults with X-linked hypophosphatemia (XLH). Methods Three groups of adults were analyzed: subjects of a clinical trial, participants in an online survey, and a subgroup of the online survey participants considered comparable to the clinical trial subjects (according to Brief Pain Inventory worst pain scores of ≥4). In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Adults with XLH also have a substantial burden of disease, related to ongoing effects of hypophosphatemia, osteomalacia, enthesopathy, osteoarthritis, bone pain, and fractures ( 39 ). A 24-week, randomized, double-blind, placebo-controlled trial in adults with XLH and chronic pain demonstrated improvements in serum phosphorus, while bone turnover markers increased, with improvements in pain, stiffness, physical function, and mobility ( 42 , 118 ).…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Adults with XLH also have a substantial burden of disease, related to ongoing effects of hypophosphatemia, osteomalacia, enthesopathy, osteoarthritis, bone pain, and fractures ( 39 ). A 24-week, randomized, double-blind, placebo-controlled trial in adults with XLH and chronic pain demonstrated improvements in serum phosphorus, while bone turnover markers increased, with improvements in pain, stiffness, physical function, and mobility ( 42 , 118 ).…”
Section: Managementmentioning
confidence: 99%
“…While enthesopathy and osteoarthritis are often debilitating features in adults with XLH, there are no data that conventional therapy or burosumab prevents or improves these in humans or mouse models ( 39 , 119-121 ). The burosumab trials could not evaluate changes in structural abnormalities of osteophytes and enthesopathy, since enthesopathy and osteoarthritis develop over many years.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Since XLH presents with a number of symptoms and signs in addition to the musculoskeletal system, the expert in metabolic bone diseases needs to be at the center of patient care and coordinate and collaborate with other professionals. Evidence for the disease burden of XLH during adulthood, as early as 20 years of age, is accumulating [2,[18][19][20][21][22][23][24]. In addition, a new therapy targeting FGF23 has been developed and applied to clinical practice for children and adults [25][26][27].…”
Section: Team Managementmentioning
confidence: 99%